The importance of the public acceptance theory in determining the success of the vertical farming projects - Kalantari, Fatemeh; Mohd Tahir, Osman; Akbari Joni, Raheleh; Amiludin, Nur Azemah (Academia de Studii Economice, 2018)
The main point is what is the role of public acceptability? The relevant question is how the public reacts and how we change our socio-cultural perception of Vertical Farming as a new technology or new innovation. The answer shows us the importance of study in related to the of Vertical Farming. There is a lack of comprehensive empirical studies exploring the status quo of Vertical Farming in all its different forms and functions. Existing empirical studies mostly focus on the construction technology or the agricultural technique of Vertical Farming. So far, no research addressed the factors contributing to the acceptance or rejection of Vertical Farming. The present research hopes to fill this gap and contribute to a better awareness of that. In this study, public acceptance as one of the important factor of accepting or rejecting the Vertical Farming is discussed and reviewed by qualitative approach. A comprehensive literature reviewed on public acceptance of Vertical Farming in relation to the food security. The study resources were formed from different sources from 2007 to 2017. Through its broad theoretical coverage, this research provides the valuable groundwork for future studies on public acceptance of Vertical Farming. Also, this body of research shed light on practical experiences or ways to solve current problems, and hope to encourage innovation or repeat projects that were successfully implemented elsewhere in the world.